(3eaGJjM GdCSQGQ heUGHjM GdCHQGQ aj JaSjQ GdbQBfs - (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s ((3GHQGgje Hf eMeO Hf GdeDjO GHh GdeLGeY GdMehi GdLhjfi s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf dLejY eMGeOg cdgG abGd YR ef bGFd (B( (3dbO ef Gddg Ydi GdeDefjf EP HYK ajge QShdkG ef CfaSge jJdhG Ydjge CjGJg hjRcjge hjYdege GdcJGH hGdMceI hGf cGfhG ef bHd dai VdGd eHjf (B) s
(3BNQgG (B:s
(3GdGjI GdGNjQI ef GdShQI hgj Cfg GdEjeGf HGddg hedGFcJg hcJHg hQSdg hBjI GdSeY hGdWGYI hJcdja GdhSY hGdWGbI hBjI GdOYG HWdH GdYah hGdeZaQI hGdQMeI hGdfUQ Ydi Gdbhe GdcGaQjf s
(3GdeLdO GdChd ai JaSjQ ShQI GdaGJMI hGdHbQIs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3fSNI fajSI LOkG s
(3cJHJ gPg GdfSNI Yf fSNI GdeUfa s
(3bQf GdfSN (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs